The changing face of science communication, technology, extension and improved decision-making at the farm-water quality interface. (August 2021) - Davis, Aaron M.; Webster, Anthony J.; Fitch, Peter; Fielke, Simon; Taylor, Bruce M.; Morris, Sheriden; Thorburn, Peter J.
Abstract: In recent decades, significant advances have been made in understanding the generation, fates and consequences of water quality pollutants in the Great Barrier Reef ecosystem. However, skepticism and lack of trust in water quality science by farming stakeholders has emerged as a significant challenge. The ongoing failures of both compulsory and particularly voluntary practices to improve land management and reduce diffuse agricultural pollution from the Great Barrier Reef catchment underlines the need for more effective communication of water quality issues at appropriate decision-making scales to landholders. Using recent Great Barrier Reef catchment experiences as examples, we highlight several emerging themes and opportunities in using technology to better communicate land use-water quality impacts and delivery of actionable knowledge to farmers, specifically supporting decision-making, behavior change, and the spatial identification of nutrient generation 'hotspots' in intensive agriculture catchments. We also make recommendations for co-designed monitoring-extension platforms involving farmers, governments, researchers, and related agencies, to cut across stakeholder skepticism, and achieve desired water quality and ecosystem outcomes. Highlights: Local data and farming stakeholder co-design of water quality monitoring cuts across trust barriers in science Water quality sensor technologies greatly increase accessibility, timeliness and relevance of monitoring data to landholders Embedding these new technologies into stakeholder decision making requires increasingly trans-disciplinary research Researcher and non-academic stakeholder collaborations increase the legitimacy and ownership of sustainability challenges Greater scientific credibility and accountability in environmental issues is required to identify future solutions